Selective Desulfurization of Dibenzothiophene by Rhodococcus erythropolis D-1 - Izumi, Yoshikazu (1994)
A dibenzothiophene (DBT)-degrading bacterium, Rhodococcus erythropolis D-1, which utilized DBT as a sole source of sulfur, was isolated from soil. DBT was metabolized to 2-hydroxybiphenyl (2-HBP) by the strain, and 2-HBP was almost stoichiometrically accumulated as the dead-end metabolite of DBT degradation. DBT degradation by this strain was shown to proceed as DBT → DBT sulfone → 2-HBP. DBT at an initial concentration of 0.125 mM was completely degraded within 2 days of cultivation. DBT at up to 2.2 mM was rapidly degraded by resting cells within only 150 min. It was thought this strain had a higher DBT-desulfurizing ability than other microorganisms reported previously.